2017
DOI: 10.1038/s41598-017-13858-3
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 21 causes changes in the circulating proteome indicative of chronic autoinflammation

Abstract: Trisomy 21 (T21) causes Down syndrome (DS), but the mechanisms by which T21 produces the different disease spectrum observed in people with DS are unknown. We recently identified an activated interferon response associated with T21 in human cells of different origins, consistent with overexpression of the four interferon receptors encoded on chromosome 21, and proposed that DS could be understood partially as an interferonopathy. However, the impact of T21 on systemic signaling cascades in living individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
158
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(173 citation statements)
references
References 93 publications
12
158
1
2
Order By: Relevance
“…Interestingly, in this previous report when these inflammatory markers were combined with measures of Aβ, they predicted AD development 15 . In further support of our findings, another report describes increased IL-6, VEGF-A, MCP-1, IL-22, and TNFα, but not other cytokines, in adults aged 20-65 with DS 55 . In contrast, a previous study of adults (mean age 30 years in DS and controls) found elevated serum MIP-1α, but not IFNγ, TNFα, MIP-1β, RANTES, or IL-6 56 .…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, in this previous report when these inflammatory markers were combined with measures of Aβ, they predicted AD development 15 . In further support of our findings, another report describes increased IL-6, VEGF-A, MCP-1, IL-22, and TNFα, but not other cytokines, in adults aged 20-65 with DS 55 . In contrast, a previous study of adults (mean age 30 years in DS and controls) found elevated serum MIP-1α, but not IFNγ, TNFα, MIP-1β, RANTES, or IL-6 56 .…”
Section: Discussionsupporting
confidence: 91%
“…Considering the potential role of IL‐10 in acquisition of tolerance, the defect in IL‐10 might contribute to delay in FPIES resolution. Increased TNF‐α in Down syndrome patients might confer predisposition to FPIES …”
Section: Different Phenotypes Of Food Protein‐induced Enterocolitis Smentioning
confidence: 99%
“…Increased TNF-α in Down syndrome patients might confer predisposition to FPIES. 46,47 T cells have long been incriminated in the FPIES pathophysiology. 48,49 However, although higher proliferation of peripheral mononuclear cells (PBMCs) after stimulation with the causal antigen has been found in CM-FPIES patients compared to controls, a large overlap was found between the groups.…”
Section: Pathophysiology Of Food Protein-induced Enterocolitis Syndmentioning
confidence: 99%
“…4e). Finally, we used public datasets and summary statistics from SomaScan proteomic studies focusing on agerelated diseases including Alzheimer's Disease (AD) 26 , Down Syndrome (DS) 27 and cardiovascular disease (CVD) 28 . A proteomic study predicting body mass index (BMI) 29 based on the plasma proteome was used as a control since weight gain varies widely with age according to data from the US National Health and Nutrition Examination Study 30 ( Supplementary Fig.…”
Section: Proteins Linked To Age-related Diseases Are Enriched In Distmentioning
confidence: 99%